STUDIES ON THE PATHOGENESIS OF FEVER : XVIII. ACTIVATION OF LEUKOCYTES FOR PYROGEN PRODUCTION - Moore, Douglas M. (The Rockefeller University Press, 1970)
Blood leukocytes, in contrast to exudate leukocytes, release little or no pyrogen when incubated in 0.15 M NaCl unless previously activated by exposure to endotoxin or to a protein activator that is present in acute exudate fluid. The activation process, which also occurs during phagocytosis, involves the synthesis of cellular protein, presumably related to the pyrogen molecule. Evidence is presented that generation of pyrogen in sterile inflammatory lesions depends on both the activator and the anaerobic conditions in the exudate fluid.